Use of mini-implants for mesialization of mandibular molars in Class II malocclusion: case report (Research, Society and Development, 2021)
Adult patients frequently present the absence of mandibular first molars, and the rehabilitation of these spaces is necessary, whether prosthetically or with orthodontic closure. This clinical case reports a patient who presents Class II malocclusion and maxillary crowding concomitant with the absence of mandibular first molars. It was decided to carry out the treatment with extractions of the maxillary first premolars and mesialization through mini-implant anchorage of the mandibular second molars to close the spaces of loss of the mandibular first molars. The results were quite satisfactory. The orthodontic movement did not cause significant side effects, and mini-implants played a fundamental role in preventing a change in the patient's profile. It is concluded that mini-implant anchorage can be effective for the mesialization of mandibular molars with minimal effects on the periodontium and profile.